360º Hypervideo - Neng, Luís António da Rosa (2011)
In traditional video, the user is locked to the angle where the camera was pointing to during the capture of the video. With 360º video recording, there are no longer these boundaries, and 360º video capturing devices are becoming more common and affordable to the general public. Hypervideo stretches boundaries even further, allowing to explore the video and to navigate to related information. By extending the hypervideo concept into the 360º video, which we call 360º hypervideo, new challenges arise. Challenges for presenting this type of hypervideo include: providing users with an appropriate interface capable to explore 360º contents, where the video should change perspective so that the users actually get the feeling of looking around; and providing the appropriate affordances to understand the hypervideo structure and to navigate it effectively in a 360º hypervideo space, even when link opportunities arise in places outside the current viewport. In this thesis, we describe an approach to the design and development of an immersive and interactive interface for the visualization and navigation of 360º hypervideos. Such interface allow users to pan around to view the contents in different angles and effectively access related information through the hyperlinks. Then a user study was conducted to evaluate the 360º Hypervideo Player’s userinterface and functionalities. By collecting specific and global comments, concerns and suggestions for functionalities and access mechanisms that would allow us to gain more awareness about the player usability and identify directions for improvements and finally we draw some conclusions and opens perspectives for future work.